Site-Specific Stabilization of DNA by a Tethered Major Groove Amine, 7-Aminomethyl-7-deaza-2′-deoxyguanosine - Szulik, Marta W. (American Chemical Society, 2013)
[Image: see text] A cationic 7-aminomethyl-7-deaza-2′-deoxyguanosine (7amG) was incorporated site-specifically into the self-complementary duplex d(G(1)A(2)G(3)A(4)X(5)C(6)G(7)C(8)T(9)C(10)T(11)C(12))(2) (X = 7amG). This construct placed two positively charged amines adjacent to the major groove edges of two symmetry-related guanines, providing a model for probing how cation binding in the major groove modulates the structure and stability of DNA. Molecular dynamics calculations restrained by nuclear magnetic resonance (NMR) data revealed that the tethered cationic amines were in plane with the modified base pairs. The tethered amines did not form salt bridges to the phosphodiester backbone. There was also no indication of the amines being capable of hydrogen bonding to flanking DNA bases. NMR spectroscopy as a function of temperature revealed that the X(5) imino resonance remained sharp at 55 °C. Additionally, two 5′-neighboring base pairs, A(4):T(9) and G(3):C(10), were stabilized with respect to the exchange of their imino protons with solvent. The equilibrium constant for base pair opening at the A(4):T(9) base pair determined by magnetization transfer from water in the absence and presence of added ammonia base catalyst decreased for the modified duplex compared to that of the A(4):T(9) base pair in the unmodified duplex, which confirmed that the overall fraction of the A(4):T(9) base pair in the open state of the modified duplex decreased. This was also observed for the G(3):C(10) base pair, where αK(op) for the G(3):C(10) base pair in the modified duplex was 3.0 × 10(6) versus 4.1 × 10(6) for the same base pair in the unmodified duplex. In contrast, equilibrium constants for base pair opening at the X(5):C(8) and C(6):G(7) base pairs did not change at 15 °C. These results argue against the notion that electrostatic interactions with DNA are entirely entropic and suggest that major groove cations can stabilize DNA via enthalpic contributions to the free energy of duplex formation.